Synthesis of Sodium Lignosulfonate (SLS) Surfactant and Polyethylene Glycol (PEG) as Surfactants in Enhanced Oil Recovery (EOR). Issue 1 (February 2021) - Dasilva, Teodora; Sudrajat, Ronny Windu; Kasmiyatun, Mega; Priyanto, Slamet; Suherman,; Pramudono, Bambang; Elmushidi, Azka Donan; Fauzan, Ahmad
Abstract: The process of extracting oil from oil wells still uses the premier and secondary methods, another method that is not optimal is the tertiary method to increase oil recovery. The tertiary method is by chemical injection with surfactants, polymers, and alkalis, among others. Surfactants (surface active agents) can change the interface tension of insoluble liquids. One of the surfactants that can be used is sodium lignosulfonate (SLS). In this study, sodium lignosulfonate surfactant was made from lignin as raw material isolated from black liquor. In this study, the surfactant sodium lignosulfonate was reacted with polyethylene glycol (PEG) as a polymer so that it became a polymeric surfactant. The surfactant polymer that has been synthesized can control oil mobility due to its viscous nature in aqueous solutions. This study examines the effect of the molecular weight of polyethylene glycol and sodium lignosulfonate, temperature, the concentration of ammonium persulfate catalyst, the weight ratio of polyethylene glycol and sodium lignosulfonate. FTIR test results on sodium lignosulfonate surfactant have a wavelength of 3369 cm −1 hydroxyl groups -OH, 1593 cm −1 -C=O aromatic groups, 1456 cm −1 -S = O groups, 1423 cm −1 -CH aromatic groups, 1216 cm −1 asymmetric SO2 groups, =C= S, and 1102cm −1 symmetric groups SO2 =C=S. The compatibility test of enhanced oil recovery (EOR) shows that SLS is compatible with the formation of water. Filtration test of enhanced oil recovery shows that SLS using membrane 42 produces greater FR solution.